Pengaruh Harga, Brand Image Dan Product Quality Terhadap Pembelian Ulang Ice Cream Mixue (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Ananda Putri Suryaningtyas; Muhammad Ridwan Basalamah; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Ice cream is a cold food made from milk which is widely consumed by the public as a thirst quenching snack. In this modern era and people's large purchasing power, ice cream entrepreneurs in Indonesia are competing to market their products, they create uniqueness starting from the process of making ice cream to the choices of flavors available. Especially with climatic conditions that affect consumer buying interest, such as Indonesia with a tropical climate. One of them is Ice Cream Mixue which was able to attract many consumers at the beginning of its presence. Mixue strives to create quality products and have more value than other products. It has been proven that since the beginning of 2022 until now, Mixue has managed to expand its outlets to remote areas of Malang. Entrepreneurs compete competitively in maintaining their companies, one of the factors is repurchase. therefore to increase the supporting factors of interest in repurchasing ice cream mixue such as price, brand image, and product quality. This research was conducted to determine the effect of price, brand image and product quality on repeat purchases. The study population was students of the Faculty of Economics and Business at the Malang Islamic University who had bought ice cream mixue. This study uses 80 respondents. Data analysis using SPSS with multiple linear analysis techniques. The results of this study indicate that the variable price, brand image and product quality simultaneously influence the repurchase of Mixue ice cream. Keywords: Repurchase, Price, Brand Image And Product Quality.